Pyogenic liver abscess caused by Salmonella Enteritidis: A rare case report - Rakesh Kumar Mahajan; Shweta Sharma; Preeti Madan; Nandini Duggal (Wolters Kluwer Medknow Publications, 2014)
Salmonella Enteritidis is one of the most important serovars transmitted from animals to humans and a serovar most commonly reported worldwide. Infection with Enteritidis is mainly limited to the intestinal tract, but under certain circumstances may cross the mucosal barrier to disseminate and get established as some localized infectious focus. Although cited as one of the very uncommon causes, Enteritidis may involve the liver and evolve into an overt abscess. Pyogenic liver abscess by a gas forming organism like Enteritidis usually follow a serious fulminant course and associated morbidity and mortality is unacceptably high unless immediate therapeutic interventions are initiated.